WHAT MOTIVATES PEOPLE TO PARTICIPATE IN A NON-COMPETITIVE GYMNASTICS FESTIVAL? - A CASE STUDY OF WORLD GYMNAESTRADA - Bortoleto Marco; Thomas Heinen; Sun Jun; Eliana Toledo; Laurita Schiavon; Lívia Pasqua; Mauricio Oliveira; Fernanda Menegaldo (University of Ljubljana Press (Založba Univerze v Ljubljani), 2019)
Sport participation might have very different goals, especially for non-competitive events. This study analyses the motivation of participants to join in the XV World Gymnaestrada in Helsinki in 2015, which is considered one of the largest international non-competitive gymnastics festival worldwide. Methods: The Goal Content for Exercise Questionnaire (GCEQ) was applied to 86 adults (56 female/ 30 male) and analyzed statistically. In addition, 24 short interviews were conducted and the data were analyzed by a Content Analysis. Results: "Social Affiliation" and "Skill Development" seem to be the principal motivations. Both are more important for women than for men. "Social Recognition" was also of particular relevance for the participants. Finally, the number of WG participations shows the same tendency in motivation for beginners and very experienced participants.